2018
DOI: 10.3390/molecules23102495
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulation Study on the Stereo Reactions between Atomic Oxygen Anion and Methane

Abstract: Ion–molecule reaction between atomic oxygen anion (O−) and methane (CH4) has been systematically investigated employing the on-the-fly ab initio molecular dynamics simulations. Besides the major H-abstraction process as the exothermic reaction studied widely, an endothermic pathway to produce OCH3− and H is also observed in this study. Three typical O− attack modes with reference to the pyramid structure of CH4 fixed in space have been considered. It was found that the internal motions of the radical products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Their findings concluded that this reaction proceeds predominantly via a direct mechanism. This is supported by the recent on-the-fly molecular dynamics simulations, which found predominantly direct dynamics at collision energies above 1.5 eV …”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Their findings concluded that this reaction proceeds predominantly via a direct mechanism. This is supported by the recent on-the-fly molecular dynamics simulations, which found predominantly direct dynamics at collision energies above 1.5 eV …”
Section: Introductionsupporting
confidence: 65%
“…This is supported by the recent on-thefly molecular dynamics simulations, which found predominantly direct dynamics at collision energies above 1.5 eV. 24 Here, we present experimental reactive scattering data for reaction 1 using a velocity map imaging (VMI) spectrometer in combination with the crossed-beam technique. We obtained experimental energy-and angle-dependent differential scattering cross sections for the OD − product anion in the energy range of 0.2−1.5 eV relative collision energy.…”
Section: ■ Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The nucleophilicity of gold is important in oxidative reactions, the Au − anion is more nucleophilic than Au(0), Au(I), and Au(III) species, and thus reactions of atomic Au − anions with hydrocarbons in the gas phase were studied [ 14 , 19 ]. The study of gas-phase ion-molecule reactions provides mechanistic insights into the bond-breaking and -making steps that are often obscured under condensed-phase environments, which are complicated by solvents, counterions, and ligands [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Although gas-phase obtained information cannot replace that of the condensed phase, understanding the intrinsic unit makes it more feasible to improve chemical reactions or catalysts from a bottom-up approach [ 20 , 22 , 26 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Ois also considered as a radical because it has an unpaired electron in its outermost orbit. It was found that atomic Ohad extremely high oxidation and reactivity towards the hydrocarbons' small molecules [23][24][25][26]. Moreover, Omay be one of the most reactive oxygen species and therefore has various potential applications, such as a one-step synthesis of phenol from benzene [27], the reduction of NO [28], and the dissociation and oxidation of bio-oil [29,30].…”
Section: Introductionmentioning
confidence: 99%